EVALUATION OF PESTICIDE RESIDUES AND POLYCYCLIC AROMATIC HYDROCARBONS CONTAINED IN SOME INSECT SPECIES CONSUMED IN TOGO - FÈGBAWÈ BADANARO; EDMOND A. DUÉ (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This study assesses the pesticide residues and Polyclic Aromatic Hydrocarbons (PAHs) contamination risks associated with the consumption of insects in Togo. The results of this research have shown that Desethylatrazine and Diuron were two herbicides found in some species. Acanthacris ruficornis (Serville, 1839) (Orthoptera: Acrididae) and Imbrasia obscura (Butler, 1878) (Lepidoptera: Saturniidae) were found to contain Desethylatrazine at 0.320 and 0.640 µg·kg-1 respectively, while Oryctes monoceros (Olivier, 1789) (Coleoptera: Scarabaeidae) and Macrotermes bellicosus (Isoptera: Termitidae) contained Diuron at 0.217 and 0.532 µg·kg-1 respectively. Moreover, Permethrin insecticide was found only in Rhynchophorus phoenicis (Smeathman, 1781) (Coleoptera: Curculionidae) at 0.556 µg·kg-1. However, the concentration of Permethrin found in this species is low compared to the maximum residual limit recommended in animalproducts (50 µg·kg-1). Moreover, no species contains more than one pesticide. For PAHs, only Fluoranthene was found in processed Cirina forda (Westwood, 1849) (Lepidoptera: Saturniidae) (0.31 µg·kg-1) at a relatively low concentration compared to the threshold allowed in processed foods (µg·kg-1). According to our results, the insects studied had a low tendency to accumulate pesticides that could pose risks to human health and the culinary methods of insects in Togo do not lead to the formation of PAHs.